RESENSI BUKU: MEMBUKA PEMIKIRAN BARU TENTANG BELAJAR DAN PEMBELAJARAN - Syahid, Aah Ahmad (Universitas Pendidikan Indonesia, 2016)
The development of learning in primary schools produced many theories and new methods to complement the competence of teachers in the 21st century. To complement the skills of teachers is needed guidelines, which describe the tasks and role of the teacher in guiding the learning from effective planning, selecting the right materials and media, implementation and evaluation are meaningful to development of students' abilities. This book review will show teachers the skills needed of today and future, will answer the challenges of teaching and learning revolution in the 21st century.Keywords: teaching and learning, the implementation of 21st century learning, the teacher of the 21st century.